(untitled) (Research, Society and Development, 2021)
Modeling and simulation applied to level control of oil and gas separators in production facilities is a very important tool because makes possible to perform tests that probably could not be viable due to operation and safety constraints. Asides the level dynamics can be well understood regarding the physical model, there will always be non-linearities to approach using a system identification procedure, requiring reasonable care on linear model identification. In order to assure a desired control performance, an adaptive control strategy has been proposed for level control for an oil and gas separator using the gain scheduling technique. Based on a first order process without time delay, the static gain and time period were determined for each point inside the operational space range of the equipment and by Internal Model Control (IMC), the tuning matrix found and converted into a function of operational parameters using polynomial interpolation methodology for future application in a real commercial PI controller. The horizontal separator was simulated using MATLAB/SIMULINK® and data from a real separator vessel were used to identify and validate the proposed process modeling in attempt to test an adaptive control strategy for practical applications. Once the GSC was implemented, simulations were performed over the non-linear system and results have shown better performance indexes for GSC while compared to the conventional PI controller for both servo and regulatory problems with reductions up to 17.65% for IAE, 29.88% for ISE, 16.38% for ITAE, 29.00% for ITSE and 13.20% for Control Effort (CE).